Effect of a single breeding season on the reproductive performance of beef cattle - Cubas, Antonio Carlos; Lesskiu, Carlos; Tahira, José Kazumassa; Mancio, Antonio Bento (Pesquisa Agropecuaria Brasileira, 2014)
The reproductive performance of 47 half-blood Canchim cows, systematically exposed to a breeding season from October 1st through January 31st was studied with a bull/cow ratio of 1/23. Birth rate obtained during the three years (1979 - 1981) was 61,7%. Year was a significant (P<0,05) source of variation on birth rate. The highest calving rate (82,9%) occurred in 1979 and the lowest (46,8%) in 1981. In the study of causes of linear decline in fertility among the years, it was concluded that the problem is probably correlated with the use of only one breeding season per year. Considering the three years altogether, from the 54 cows that did not calve, 27 (50%) had given birth to a calf during the second half of the birth seasons of the previous years; from the 87 cows that succeeded in calving, 72 (82,7%) had dropped their calves during the first half of the birth seasons of the previous years. The statistical analysis performed through the X-square test showed significance at the (P<0,001) level, indicating that the tendency of cows calving in the second half of the birth season not to have a calf in the following year could not be accounted for as by chance. These results indicate that, on conditions of natural grazing without supplementation, only one single breeding season per year tends to reduce fertility of cows.